Strategies to reduce hyperglycemia-related anxiety in elite athletes with type 1 diabetes: A qualitative analysis - Katz, A.; Shulkin, A.; Fortier, M.-A.; Yardley, J. E.; Kichler, J.; Housni, A.; Talbo, M. K.; Rabasa-Lhoret, R.; Brazeau, A.-S. (PLOS ONE, 2025)
Objective Managing blood glucose levels is challenging for elite athletes with type 1 diabetes (T1D) as competition can cause unpredictable fluctuations. While fear of hypoglycemia during physical activity is well documented, research on hyperglycemia-related anxiety (HRA) is limited. HRA refers to the heightened fear that hyperglycemia-related symptoms will impair functioning. This study investigates current strategies employed to mitigate HRA during competition and the development of alternative approaches.